Coronary artery calcification and myocardial perfusion in asymptomatic adults : The MESA (Multi-Ethnic Study of Atherosclerosis) - LU WANG; JEROSCH-HEROLD, Michael; JACOBS, David R; SHAHAR, Eyal; DETRANO, Robert; FOLSOM, Aaron R (Journal of the American College of Cardiology, 2006)
This study assessed the cross-sectional association between coronary artery calcification (CAC) and myocardial perfusion in an asymptomatic population. Clinical studies showed that the prevalence of stress-induced ischemia increased with CAC burden among patients with coronary heart disease (CHD). Whether an association between CAC and myocardial perfusion exists in subjects without a history of CHD remains largely unknown. A total of 222 men and women, ages 45 to 84 years old and free of CHD diagnosis, in the Minnesota field center of the MESA (Multi-Ethnic Study of Atherosclerosis) were studied. Myocardial blood flow (MBF) was measured using magnetic resonance imaging during rest and adenosine-induced hyperemia. Perfusion reserve was calculated as the ratio of hyperemic to resting MBF. Agatston CAC score was determined from chest multidetector computed tomography. Mean values of hyperemic MBF and perfusion reserve, but not resting MBF, were monotonically lower across increasing CAC levels. After adjusting for age and gender, odds ratios (95% confidence intervals) of reduced perfusion reserve (<2.5) for subjects with CAC scores of 0, 0.1 to 99.9, 100 to 399, and > or =400 were 1.00 (reference), 2.16 (0.96 to 4.84), 2.81 (1.04 to 7.58), and 4.99 (1.73 to 14.4), respectively. Further adjustment for other coronary risk factors did not substantially modify the association. However, the inverse association between perfusion reserve and CAC attenuated with advancing age (p for interaction < 0.05). Coronary vasodilatory response was associated inversely with the presence and severity of CAC in asymptomatic adults. Myocardial perfusion could be impaired by or manifest the progression to subclinical coronary atherosclerosis in the absence of clinical CHD.